Remote Sensing Advances for Earth System Science The ESA Changing Earth Science Network: Projects 2009-2011 - Fernǹdez-Prieto, Diego. (SpringerBriefs in Earth System Sciences, 2013)
The European Space Agency, through its Support to Science Element (STSE) Programme, funds a network of young post-doc scientists undertaking cutting-edge research in the area of Remote Sensing. This so-called Changing Earth Science Network focuses on the exploitation of Earth Observation (EO) data to address major issues related to the broader context of Climate Change under five scientific research lines: Oceans, Atmosphere, Cryosphere, Land and Solid Earth.